Intensification of heat and hydrooynamic processes in industrial vacuum pans - Garyazha, Vladimir; Artyuhov, Yuri; Didushko, Boris; Kulinchenko, Vitaliy (My University, 1978)
New methods of intensification of these processes hare been developed here purely in hydrodynamic ways: a) by the way of blowing gas into boiling tubes of vacuum pans; b) by the way of localisation of thorough boiling of massecuite in a layer of small thickness, gravitatingly flowing along the plane inclined heating surface.

Розглянуто нові методи інтенсифікації тепломасообмінних процесів, виключно гідродинамічних шляхах: a) шляхом видування газу в кипятильні труби вакуум-апаратів; b) шляхом ведення процесу на похилій поверхні теплообміну у гравітаційно стікаючій плівці киплячого утфелю.
Keywords: intensification; heat exchange; mass-transfer; methods; інтенсифікація; теплообмін; масообмін методи; кафедра процесів і апаратів харчових виробництв